2018
DOI: 10.15252/embj.201797673
|View full text |Cite
|
Sign up to set email alerts
|

AMPK promotes survival of c‐Myc‐positive melanoma cells by suppressing oxidative stress

Abstract: Although c-Myc is essential for melanocyte development, its role in cutaneous melanoma, the most aggressive skin cancer, is only partly understood. Here we used the mouse melanoma model to show that c-Myc is essential for tumor initiation, maintenance, and metastasis. c-Myc-expressing melanoma cells were preferentially found at metastatic sites, correlated with increased tumor aggressiveness and high tumor initiation potential. Abrogation of c-Myc caused apoptosis in primary murine and human melanoma cells. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…From a molecular point of view, F10503LO1 decreased the content of phospho-AKT, and phospho-AMPK, impaired angiogenesis through a decrease in the intratumor content of VEGF and decreased p53 levels suggesting a specific mechanism leading to a reduced in vivo viability of B16F10 cells and tumor dissemination. In addition, the observation that AMPK is dephosphorylated in samples of tumors treated with the drug probably contributes to cancer cell death due to the inability to provide energy substrates to the growing tumor ( 41 ). Interestingly, DTIC did not reproduce these effects, nor did it exhibit a significant synergism with F10503LO1 in terms of signaling or tumor growth arrest, prevailing the action of the benzylamine derivative over the DTIC treatment ( 5 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a molecular point of view, F10503LO1 decreased the content of phospho-AKT, and phospho-AMPK, impaired angiogenesis through a decrease in the intratumor content of VEGF and decreased p53 levels suggesting a specific mechanism leading to a reduced in vivo viability of B16F10 cells and tumor dissemination. In addition, the observation that AMPK is dephosphorylated in samples of tumors treated with the drug probably contributes to cancer cell death due to the inability to provide energy substrates to the growing tumor ( 41 ). Interestingly, DTIC did not reproduce these effects, nor did it exhibit a significant synergism with F10503LO1 in terms of signaling or tumor growth arrest, prevailing the action of the benzylamine derivative over the DTIC treatment ( 5 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment of MYC-deleted cells with 991, a highly selective pharmacological activator of AMPK [12], completely rescued both the elevated ROS and the cytotoxic effect of MYC deletion, mirroring the cytoprotective role of NUAK1 in counteracting ROS. Furthermore, as is the case for high expression of NUAK1 in CRC, high expression of AMPK in Melanoma correlates with significantly reduced overall survival of human patients [2,3].…”
mentioning
confidence: 83%
“…A separate study by Radtke and colleagues has now revealed a similar role for AMPK, or rather, for a specific subset of AMPK complexes, in MYC-dependent Melanoma [3]. Although often discussed as though it were a single entity, the AMP-activated protein kinase is a trimeric complex comprised of 1 of 2α, 1 of 2β and 1 of 3γ subunits, and there is evidence that multiple distinct complexes can assemble and co-exist in cells, presumably responding to distinct cues and/or regulating specific downstream substrates [10].…”
mentioning
confidence: 94%
See 2 more Smart Citations